Carbon Monoxide Promotes the Catalytic Hydrogenation on Metal Cluster Catalysts - Ruixuan Qin; Pei Wang; Pengxin Liu; Shiguang Mo; Yue Gong; Liting Ren; Chaofa Xu; Kunlong Liu; Lin Gu; Gang Fu; Nanfeng Zheng (Research, 2020)
Size effect plays a crucial role in catalytic hydrogenation. The highly dispersed ultrasmall clusters with a limited number of metal atoms are one candidate of the next generation catalysts that bridge the single-atom metal catalysts and metal nanoparticles. However, for the unfavorable electronic property and their interaction with the substrates, they usually exhibit sluggish activity. Taking advantage of the small size, their catalytic property would be mediated by surface binding species. The combination of metal cluster coordination chemistry brings new opportunity. CO poisoning is notorious for Pt group metal catalysts as the strong adsorption of CO would block the active centers. In this work, we will demonstrate that CO could serve as a promoter for the catalytic hydrogenation when ultrasmall Pd clusters are employed. By means of DFT calculations, we show that Pdn n=2‐147 clusters display sluggish activity for hydrogenation due to the too strong binding of hydrogen atom and reaction intermediates thereon, whereas introducing CO would reduce the binding energies of vicinal sites, thus enhancing the hydrogenation reaction. Experimentally, supported Pd2CO catalysts are fabricated by depositing preestablished [Pd2(μ-CO)2Cl4]2- clusters on oxides and demonstrated as an outstanding catalyst for the hydrogenation of styrene. The promoting effect of CO is further verified experimentally by removing and reintroducing a proper amount of CO on the Pd cluster catalysts.